Book of Abstracts of the 24th Annual Congress of the European College of Sport Science - 3rd - 6th July 2019, Prague - Czech Republic (Book of Abstracts of the 24th Annual Congress of the European College of Sport Science - 3rd - 6th July 2019, Prague - Czech Republic, 2018)
TABLE OF CONTENTS 8 WEDNESDAY, JULY 3, 2019 17 12:45 - 13:45 17 CP-PM01 MOLECULAR SIGNALING RESPONSE 17 CP-PM04 MUSCLE GROWTH: ADAPTATION 21 CP-PM05 TRAINING AND TESTING 24 CP-BN01 NEUROMUSCULAR PHYSIOLOGY 28 CP-MI01 STRENGTH AND POWER 32 CP-PM06 BONE AND MUSCLE 36 CP-SH02 CHILDREN 40 CP-PM02 ERGOGENIC AIDS; FAT, GLUCOSE AND METABOLISM 44 CP-BN02 MUSCLE / TENDON FUNCTION 47 CP-SH03 HUMANITIES 51 CP-SH04 PSYCHOLOGICAL FACTORS IN SPORT 54 CP-BN03 MOTOR LEARNING AND MOTOR CONTROL 57 CP-PM03 HEALTH AND FITNESS 60 CP-BN06 SPORT TECHNOLOGY MIXED 64 CP-BN07 SPORTS PHYSIOTHERAPY I 67 CP-BN04 BALANCE AND POSTURE 71 CP-BN05 RUNNING AND THROWING 75 CP-BN08 JUMPING AND SQUATTING 78 CP-MI02 TRAINING AND TESTING I 82 CP-SH01 PHYSICAL EDUCATION / PEDAGOGIC APPROACHES 85 14:00 - 15:30 88 IS-PM05 HIGH-CARBOHYDRATE OR HIGH-FAT DIETS FOR OPTIMISING TRAINING ADAPTATION AND PERFORMANCE? [APPLIED TRACK] 88 GSSI-PRES GSSI NUTRITION AWARD PRESENTATIONS 88 OP-PM06 ENERGY, FAT AND METABOLISM 91 OP-PM01 MOLECULARBIOLOGY AND BIOCHEMISTRY: SIGNALING AND RESPONSE 94 OP-BN01 MUSCLE AND/OR TENDON FUNCTION I 96 OP-PM15 PHYSIOLOGY 99 OP-PM12 TRAINING AND TESTING 101 OP-PM10 HEALTH AND FITNESS: CLINICAL POPULATIONS I 104 OP-SH06 PROFESSIONAL DEVELOPMENT - PHYSICAL EDUCATION AND EXERCISE SETTINGS 107 OP-MI02 TRAINING AND TESTING: RUGBY 109 OP-SH01 SOCIOLOGY 111 OP-SH05 CHILDREN 114 9 24TH ANNUAL CONGRESS OF THE EUROPEAN COLLEGE OF SPORT SCIENCE 16:00 - 17:30 115 IS-SP03 EFFECTIVE MANAGEMENT OF THE RETURN OF TRAINING (RTT) - SPONSORED BY CATAPULT [APPLIED TRACK] 115 OP-PM03 NUTRITION: VITAMINS, COLLAGEN AND ANTIOXIDANTS 116 OP-PM02 METABOLIC SYNDROME AND DIABETES I 118 OP-PM08 HEALTH AND FITNESS: CHILDREN AND ADOLESCENTS 121 OP-PM13 MUSCLE DAMAGE AND REPAIR I 124 OP-BN03 MOTOR LEARNING AND MOTOR CONTROL: FEEDBACK - TALENT - BALANCE 126 IS-BN01 STABILITY TRAINING THROUGHOUT THE LIFESPAN 129 OP-MI03 TRAINING AND TESTING 129 OP-PM09 PHYSIOLOGY: TRAINING AND TESTING 132 OP-BN06 TEAM SPORTS: SOCCER 134 OP-SH02 SPORT STATISTICS AND ANALYSES 136 OP-SH07 PSYCHOLOGY: STRESS AND ANXIETY 138 17:45 - 19:00 141 PL-PS01 SPRINGS AND SPRINTERS 141 THURSDAY, JULY 4, 2019 142 08:00 - 09:30 142 IS-MI02 ADVANCES IN ATHLETE DEVELOPMENT RESEARCH 142 OP-PM14 PHYSICAL ACTIVITY / INACTIVITY I 143 OP-PM05 LIFESTYLE: AGEING 146 OP-PM07 HORMONAL BIOLOGY 148 OP-BN02 BALANCE AND STABILITY 150 OP-BN07 SKILL ACQUISITION 153 OP-PM17 THERMOREGULATION I 155 OP-BN08 MOTOR UNIT FUNCTION I 158 OP-MI04 YOUTH FOOTBALL 160 OP-SH08 SPORT, ENVIRONMENT, GLOBALIZATION 163 OP-SH04 PHYSICAL EDUCATION AND PEDAGOGICS 164 IS-SH01 ATHLETES MENTAL HEALTH - FEPSAC SYMPOSIUM 166 09:45 - 11:15 168 IS-PM01 THE EFFECTS OF ACUTE EXERCISE AND LONG-TERM EXERCISE TRAINING ON HEART 168 IS-SP02 MULTI-DISCIPLINARY APPROACH IN PROFESSIONAL FOOTBALL: RETURN TO PLAY FROM MUSCULOSKELETAL INJURIES - SPONSORED BY GSSI 168 OP-PM04 METABOLIC FITNESS AND FLEXIBILITY 170 OP-PM11 AGEING 172 OP-BN05 GAIT I 175 OP-MI01 TRAINING AND TESTING: TALENT 177 OP-BN04 NEUROMUSCULAR PHYSIOLOGY 180 OP-PM16 ENDURANCE 183 OP-MI05 AGILITY 185 OP-SH09 HISTORY 187 OP-SH03 PSYCHOLOGY 190 IS-SH02 THE ROLE OF PERCEPTION IN SPORT 193 PRAGUE/CZECH REPUBLIC, 3-6 JULY 2019 10 11:30 - 12:45 194 PL-PS02 PERSONALIZED EXERCISE ONCOLOGY 194 13:30 - 14:30 194 CP-SH05 PSYCHOLOGY / MOTIVATION 194 CP-MI09 TEAM SPORTS 199 CP-MI12 ENDURANCE 203 CP-SH06 PSYCHOLOGICAL RESPONSES TO EXERCISE I 207 CP-SH07 PSYCHOLOGICAL RESPONSES TO EXERCISE II 210 CP-PM09 MOLECULAR BIOLOGY 213 CP-PM11 OBESITY AND WEIGHT LOSS 217 CP-SH08 TEACHING AND COACHING EFFECTS ON CHILDREN 221 CP-MI03 TRAINING AND TESTING II 225 CP-MI15 AGEING 228 CP-PM13 INJURY PREVENTION 232 CP-PM07 HYPOXIA 235 CP-PM16 VITAMINE D / OTHER SUPPLEMENTS 239 CP-PM19 ERGOGENIC AIDS / OTHER SUPPLEMENTS 242 CP-BN09 MOTOR LEARNING AND MOTOR CONTROL 244 CP-PM08 AGEING 249 CP-PM20 GENOMICS / MOLECULAR METABOLISM 253 CP-PM21 CARDIOVASCULAR ATHLETES 256 CP-PM12 GENDER 259 14:45 - 16:15 263 IS-PM02 ECCENTRIC CYCLING: BASICS AND CLINICAL APPLICATIONS [CLINICAL TRACK] 263 OP-PM18 HEALTH AND FITNESS: AGEING I 264 OP-PM19 NUTRITION: ERGOGENIC AIDS I 267 OP-PM20 MOLECULAR BIOLOGY AND BIOCHEMISTRY: GENOMICS I 269 OP-BN09 SPORTS PHYSIOTHERAPY: ACL 271 OP-MI06 HEALTH AND FITNESS 273 IS-BN02 NOT SO SIMPLE? MUSCLE-TENDON INTERACTION TO AMPLIFY OR ATTENUATE POWER IN HUMAN MOVEMENT 275 OP-BN10 TESTING AND TRAINING IN SWIMMING I 277 OP-MI07 TRAINING AND TESTING: MILITARY / MIXED 278 OP-SH11 PSYCHOLOGY: COGNITION 281 OP-SH10 SPORT MANAGEMENT 284 IS-SH03 ADVANCES IN UNDERSTANDING THE ROLE OF FUNDAMENTAL MOVEMENT SKILLS ON CHILDREN'S PHYSICAL ACTIVITY 286 16:45 - 18:15 288 IS-PM03 THE SKIN CIRCULATION AS A TARGET FOR LIFESTYLE INTERVENTION AND INNOVATION IN MEASUREMENT 288 IS-EX01 ECSS-ACSM EXCHANGE SYMPOSIUM: SPORT ELIGIBILITY AND CLASSIFICATION IN THE PARALYMPIC GAMES 288 OP-PM22 RESPIRATION / PULMONARY 289 OP-PM21 GENDER 291 OP-BN11 BIOMECHANICS: RUNNING 293 OP-BN12 NEUROMUSCULAR FATIGUE I 296 11 24TH ANNUAL CONGRESS OF THE EUROPEAN COLLEGE OF SPORT SCIENCE IS-SP01 FROM ANKLE SPRAIN TO CHRONIC ANKLE INSTABILITY AND HOW TO AVOID IT - SPONSORED BY ADIDAS [CLINICAL TRACK] 298 OP-BN13 SPORT TECHNOLOGY I 299 OP-MI08 AGEING I 301 OP-BN14 MOTOR LEARNING AND MOTOR CONTROL: TALENT - SKILLS - PERFORMANCE 304 OP-SH12 PSYCHOLOGY: MOTIVATION 306 OP-SH13 ETHICAL BEHAVIOUR IN SPORT 309 18:30 - 20:00 311 IS-PM04 EXERCISE-INDUCED MUSCLE DAMAGE: WHAT IS IT, HOW IS IT DETECTED, AND WHY IS IT INDUCED? 311 OP-PM23 CARDIAC FUNCTION AND CARDIOVASCULAR DISEASES 312 OP-PM24 RECOVERY FROM SPORTS AND EXERCISE 315 OP-BN15 BIOMECHANICS: WINTER SPORTS 317 OP-BN16 MOTOR UNIT FUNCTION II 320 IS-BN03 BRAIN STIMULATION: AN EMERGING PHENOMENON IN SPORT AND EXERCISE 323 OP-PM43 NUTRITION: SUPPLEMENTS AND DIETARY REGIMENS 324 OP-PM46 CARDIOVASCULAR PHYSIOLOGY I 326 OP-SH15 SOCIOLOGY: CHILDREN AND GENDER 328 OP-SH14 PSYCHOLOGY: HEALTH AND WELLBEING 330 IS-SH04 MOTIVATION IN PHYSICAL EDUCATION: A FOCUS ON TEACHERS ROLE THROUGH SELF-DETERMINATION THEORY 332 FRIDAY, JULY 5, 2019 334 08:00 - 09:30 334 IS-PM06 THE LUNGS DURING EXERCISE: OFTEN OVERLOOKED, OFTEN MISUNDERSTOOD [CLINICAL TRACK] 334 OP-PM26 HIGH INTENSITY INTERVAL TRAINING 335 OP-PM25 METABOLIC SYNDROME AND DIABETES II 337 OP-PM29 TEAM SPORTS: SOCCER 338 OP-BN17 SPORTS PHYSIOTHERAPY: FOOT AND ANKLE 341 OP-MI09 TEAM SPORTS I 344 IS-BN04 NEW INSIGHTS ON THE CONTROL OF VOLUNTARY ACTIONS DERIVED FROM MOTOR UNIT RECORDINGS 346 OP-PM28 HYPOXIA I 347 OP-PM27 SPORT INJURIES AND ORTHOPEDICS I 349 OP-BN18 SPORTS TECHNOLOGY II 352 OP-SH16 PSYCHOLOGY: PHYSICAL ACTIVITY PROMOTION 354 IS-SH05 THE ROLE OF SPORT HISTORY IN THE SCIENTIFIC COMMUNITY - AIMS, OPPORTUNITIES, CHALLENGES 357 09:45 - 11:15 358 IS-MI04 INDIVIDUALIZATION AND OPTIMIZATION OF EXERCISE TRAINING PRESCRIPTION [CLINICAL TRACK] 358 OP-PM30 CARDIOVASCULAR PHYSIOLOGY 359 OP-PM31 OBESITY 361 OP-PM32 MUSCLE DAMAGE AND REPAIR II 363 OP-BN19 MOTOR LEARNING AND MOTOR CONTROL: COORDINATION 366 OP-BN20 TRAINING AND TESTING IN SWIMMING II 368 IS-BN05 HAMSTRING STRAIN INJURIES: PREVENTION, REHABILITATION AND PREDICTION LESSONS FROM MONEYBALL [CLINICAL TRACK] 371 OP-BN21 GAIT II 371 PRAGUE/CZECH REPUBLIC, 3-6 JULY 2019 12 OP-PM33 HEALTHY AND FITNESS: AGEING II 374 OP-PM34 MOLECULAR BIOLOGY AND BIOCHEMISTRY: MUSCLE - INFLAMMATION - MITOCHONDRIA 376 IS-SH06 SUSTAINABLE SPORT TOURISM - CHALLENGES FOR THE FUTURE 378 11:30 - 12:45 379 PL-PS03 SPORT AND BRAIN INJURIES - A RED FLAG FOR SPORT? 379 13:30 - 14:30 380 CP-SH09 MORALITY AND CHARACTER DEVELOPMENT 380 CP-MI10 STRENGTH AND POWER 384 CP-MI13 SWIMMING 387 CP-SH10 TEAM FUNCTIONING AND LEADERSHIP 391 CP-SH11 EXERCISE, COGNITION AND PERFORMANCE I 394 CP-PM10 ORTHOPEDICS 397 CP-MI16 APP AND METHOD DEVELOPMENT 401 CP-SH12 EXERCISE, COGNITION AND PERFORMANCE II 405 CP-MI04 TRAINING AND TESTING III 408 CP-PM17 CHILDREN 412 CP-PM18 TEAM SPORTS 416 CP-MI07 MIXED II 420 CP-BN10 SPORTS PHYSIOTHERAPY I 424 CP-PM22 AMINO ACIDS, FAT, GLUCOSE AND METABOLISM 427 CP-PM23 ENDURANCE METHODS: RECOVERY 430 CP-PM24 DISEASE AND PHYSICAL ACTIVITY 434 CP-PM25 CARDIOVASCULAR MIXED 437 CP-PM27 HORMONAL 441 CP-PM28 PHYSIOLOGY AND MEDICINE: MIXED 445 CP-PM26 EVALUATION OF DIET QUALITY; NUTRITION KNOWLEDGE 448 14:45 - 16:15 450 IS-PM07 LOOKING INSIDE-OUT INTO AGEING SKELETAL MUSCLE: HORMONES, SYSTEMIC INFLAMMATORY ENVIRONMENTAND THE EXTRACELLULAR MATRIX 450 OP-PM35 INTERVAL TRAINING 451 OP-PM36 NUTRITION: ERGOGENIC AIDS II 453 OP-PM37 FATIGUE 455 OP-MI11 CYCLING 458 OP-MI10 STRENGTH AND POWER I 460 OP-BN22 MUSCLE AND/OR TENDON FUNCTION II 463 OP-BN23 SPORTS TECHNOLOGY III 466 OP-PM38 TEAM SPORTS: CHILDREN 468 OP-PM39 HEALTH AND FITNESS: PREGNANCY - HIIT - TIMING OF EXERCISE 471 IS-MI03 SPORT FOR ATHLETES WITH DISABILITY: CLASSIFICATION RESEARCH, SMART MONITORING TECHNOLOGY 473 OP-PM44 NUTRITION: CARBOHYDRATES AND DIETARY REGIMENS 474 16:45 - 18:15 476 IS-PM08 A WARM BATH, GLASS OF (CHOCOLATE) MILK AND A COMFORTABLE MATTRESS: OPTIMIZING RECOVERY OF EXERCISE PERFOMANCE [APPLIED TRACK] 476 13 24TH ANNUAL CONGRESS OF THE EUROPEAN COLLEGE OF SPORT SCIENCE IS-EX02 ECSS-JSPFSM EXCHANGE SYMPOSIUM: LACTATE/PYRUVATE METABOLISM IN SKELETAL MUSCLE: ENERGY SUBSTRATES AND BEYOND 477 OP-PM40 FAT, GLUCOSE AND METABOLISM 478 OP-PM45 NUTRITION: PROTEIN AND DIETARY REGIMENS 480 OP-PM52 HEALTH AND FITNESS: CARDIOVASCULAR 482 OP-PM51 EXERCISE THERAPY 484 OP-MI13 MIDDLE - LONG DISTANCE RUNNING 487 OP-MI12 TEAM SPORTS: SOCCER 489 OP-PM50 MOLECULAR BIOLOGY AND BIOCHEMISTRY: GENOMICS II 492 OP-PM59 MOLECULAR BIOLOGY AND BIOCHEMISTRY: MICROBIOTA - METABOLISM 494 OP-BN24 PARALYMPICS 496 IS-SH07 ECONOMIC, SOCIOLOGICAL, PEDAGOGICAL AND ETHICAL APPROACHES TO E-SPORTS 498 18:30 - 20:00 500 IS-PM09 IMAGING THE FUTURE OF ELITE SPORTS WITH METABOLIC MAGNETIC RESONANCE INNOVATIONS 500 IS-PM10 THE MASTERS ATHLETE: PERFORMANCE, RECOVERY AND HEALTH CONSIDERATIONS [APPLIED TRACK] 501 OP-PM41 NUTRITION: AMINO ACIDS AND PROTEINS 502 OP-PM47 CARDIOVASCULAR PHYSIOLOGY II 505 OP-PM55 HEALTH AND FITNESS: SEDENTARY LIFESTYLE 507 OP-PM56 HYPOXIA II 509 IS-BN06 (IM)BALANCE OF MUSCLE AND TENDON ADAPTATION IN HIGH LEVEL SPORTS 511 OP-BN25 SPORTS PHYSIOTHERAPY: BACKPAIN 512 OP-MI14 AGEING II 514 OP-BN26 SPORT TECHNOLOGY IV 516 OP-PM53 HEALTHY AND FITNESS: CLINICAL POPULATIONS II 519 OP-PM54 SPORT INJURIES AND ORTHOPEDICS II 521 SATURDAY, JULY 6, 2019 524 08:00 - 09:30 524 IS-PM11 REASONS AND REMEDIES FOR THE AGE-RELATED DECLINE IN SKELETAL MUSCLE ADAPTABILITY 524 OP-PM42 NUTRITION: OTHER SUPPLEMENTS 525 IS-EX03 CSSS-ECSS EXCHANGE SYMPOSIUM: SUPPORT SYSTEM FOR ELITE ATHLETES AND PUBLIC HEALTH 527 OP-PM48 CARDIOVASCULAR PHYSIOLOGY III 528 OP-BN27 NEUROMUSCULAR FATIGUE II 531 OP-MI15 STRENGTH AND POWER II 533 OP-BN28 JUMPING AND SQUATTING 536 OP-BN29 MOTOR LEARNING AND MOTOR CONTROL: CHILDREN 538 OP-PM58 ENDURANCE: WINTER SPORTS 541 OP-PM71 INJURY PREVENTION III 543 IS-MI05 CONSUMER DIGITAL TECHNOLOGIES FOR HEALTH AND SPORTS PERFORMANCE 546 IS-SH08 'SPORT' - PUBLIC HEALTH OR PUBLIC HARM? 547 09:45 - 11:15 548 IS-PM12 CARDIAC, VASCULAR AND CEREBROVASCULAR ADAPTATION TO HYPOXIA AT REST AND DURING EXERCISE; LESSONS FROM HIGH ALTITUDE NATIVES 548 IS-MI01 THE NEUROSCIENCE AND INTERPRETATION OF PLACEBO EFFECTS IN SPORTS AND EXERCISE 548 PRAGUE/CZECH REPUBLIC, 3-6 JULY 2019 14 OP-PM57 TRAINING AND TESTING: ENDURANCE 549 OP-MI16 RUNNING 552 OP-PM66 PHYSIOLOGY: MUSCLE METABOLISM 554 OP-MI18 TEAM SPORTS II 556 OP-PM63 STRENGTH 559 OP-BN30 INJURY PREVENTION 561 OP-PM65 MIXED SPORTS 564 OP-PM68 HEALTH AND FITNESS: BRAIN, MENTAL AND MIXED 565 OP-PM70 PHYSICAL ACTIVITY / INACTIVITY II 568 11:30 - 13:00 570 IS-PM13 DIETARY NITRATE AND HYPOXIA 570 OP-PM60 THERMOREGULATION II 571 OP-PM61 CHILDREN 573 OP-PM62 MOLECULAR BIOLOGY AND BIOCHEMISTRY: METABOLOMICS - PROTEOMICS 575 OP-MI17 STRENGTH AND POWER III 577 OP-PM64 PHYSICAL ACTIVITY FOR OLDER PEOPLE 580 IS-BN07 TOWARDS A BETTER UNDERSTANDING OF RUNNING INJURIES [CLINICAL TRACK] 582 OP-BN31 BIOMECHANICS AND NEUROMUSCULAR: MIXED I 583 OP-BN32 BIOMECHANICS AND NEUROMUSCULAR: MIXED II 586 OP-PM67 SPORTS INJURIES AND ORTHOPEDICS III 588 OP-PM69 HEALTH AND FITNESS: CLINICAL POPULATIONS II 590 13:45 - 14:45 593 CP-MI14 RUNNING 593 CP-MI05 TRAINING AND TESTING IV 596 CP-MI08 MIXED III 600 CP-MI17 RAQUET SPORTS 604 CP-PM14 TALENT / ELITE ATHLETES 608 CP-BN11 SPORTS PHYSIOTHERAPY II 612 CP-MI11 COMBAT SPORTS 615 CP-PM29 METABOLISM AND OTHER 619 CP-PM30 PHYSICAL DISABILITIES AND THERMOREGULATION 622 CP-PM15 PHYSICAL ACTIVITY / INACTIVITY 626 CP-SH13 MIXED 630 CP-PM31 MIXED 634 CP-PM32 CARDIOVASCULAR: YOUNG 638 15:15 - 16:30 642 PL-PS04 THE IMPORTANCE OF CIRCADIAN RYTHM FOR ATHLETIC PERFORMANCE AND SKELETAL MUSCLE HEALTH 642 E-POSTER NOT DEBATED 643 PP-UD01 643 BIOMECHANICS 643 COACHING 659 DISABILITY SPORT AND PHYSICAL ACTIVITY 667 15 24TH ANNUAL CONGRESS OF THE EUROPEAN COLLEGE OF SPORT SCIENCE HEALTH AND FITNESS 670 HISTORY 688 MOLECULAR BIOLOGY AND BIOCHEMISTRY 689 MOTOR LEARNING AND MOTOR CONTROL 694 NEUROMUSCULAR PHYSIOLOGY 697 NUTRITION 698 PHILOSOPHY AND ETHICS 706 PHYSICAL EDUCATION AND PEDAGOGICS 707 PHYSIOLOGY 710 PSYCHOLOGY 724 REHABILITATION AND (SPORTS)PHYSIOTHERAPY 737 SOCIOLOGY 742 SPORT MANAGEMENT AND LAW 746 SPORT STATISTICS AND ANALYSES 748 SPORT TECHNOLOGY 752 SPORTS MEDICINE AND ORTHOPEDICS 758 TRAINING AND TESTING 767